2016
DOI: 10.1016/j.ntt.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of adolescent nicotine exposure in rats: Evidence for cognitive deficits in adult female offspring

Abstract: This study investigated whether adolescent nicotine exposure in one generation of rats would impair the cognitive capacity of a subsequent generation. Male and female rats in the parental F0 generation were given twice-daily i.p. injections of either 1.0 mg/kg nicotine or an equivalent volume of saline for 35 days during adolescence on postnatal days 25-59 (P25-59). After reaching adulthood, male and female nicotine-exposed rats were paired for breeding as were male and female saline control rats. Only female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the learning and memory systems involved depend on different behavioral and neural systems as shown by dissociations observed in adulthood long after chronic adolescent drug exposure (Pickens et al, 2013;Renaud et al, 2015;Rowan et al, 2015;Renaud and Fountain, 2016;Sharp et al, 2019). Similar dissociations of cognitive behavioral systems can be seen in normal rats administered acute muscarinic cholinergic blockade (Pickens et al, 2013;Renaud et al, 2015;Rowan et al, 2015;Renaud and Fountain, 2016;Sharp et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the learning and memory systems involved depend on different behavioral and neural systems as shown by dissociations observed in adulthood long after chronic adolescent drug exposure (Pickens et al, 2013;Renaud et al, 2015;Rowan et al, 2015;Renaud and Fountain, 2016;Sharp et al, 2019). Similar dissociations of cognitive behavioral systems can be seen in normal rats administered acute muscarinic cholinergic blockade (Pickens et al, 2013;Renaud et al, 2015;Rowan et al, 2015;Renaud and Fountain, 2016;Sharp et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, the learning and memory systems involved depend on different behavioral and neural systems as shown by dissociations observed in adulthood long after chronic adolescent drug exposure (Pickens et al, 2013;Renaud et al, 2015;Rowan et al, 2015;Renaud and Fountain, 2016;Sharp et al, 2019). Similar dissociations of cognitive behavioral systems can be seen in normal rats administered acute muscarinic cholinergic blockade (Pickens et al, 2013;Renaud et al, 2015;Rowan et al, 2015;Renaud and Fountain, 2016;Sharp et al, 2019). The SMC method in mice and rats produces data comparable to data in humans in an analogous task (Fountain and Rowan, 1995) and rats use multiple cognitive processes concurrently: rule-learning, stimulus-response (S-R) learning, discrimination learning, and multiple-item memory Fountain, 2010, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrating that the dopamine neurotransmitter mechanisms impacted by the prenatal nicotine exposure were transmitted transgenerationally as well (Zhu et al, 2014). Since then, a number of studies in human subjects (Golding et al, 2017(Golding et al, , 2020 as well as animal models (Buck et al, 2019;Liu et al, 2020;Renaud & Fountain, 2016;Yohn et al, 2015) have shown transgenerational transmission of traits following in utero nicotine exposure.…”
Section: Transgenerational Transmission Of Adhd-associated Traits In ...mentioning
confidence: 99%
“…measured using a serial multiple-choice task [ 52 ]. Currently, the mechanism(s) underlying the cross-generational consequences of nicotine exposure in adolescence are not well understood but suggest epigenetic modifications of the genome and future work should focus on the cellular events underlying the development of these phenotypic traits.…”
Section: Nicotinementioning
confidence: 99%